2021
DOI: 10.3389/fgene.2021.717533
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Polymorphism of Vitamin D Family Genes CYP2R1, CYP24A1, and CYP27B1 Are Associated With a High Risk of Non-alcoholic Fatty Liver Disease: A Case-Control Study

Abstract: BackgroundPrevious studies have highlighted the important role of vitamin D and calcium pathway genes in immune modulation, cell differentiation and proliferation, and inflammation regulation, all closely implicated in the pathogenesis of non-alcoholic fatty liver disease (NAFLD).ObjectiveThis study aims to investigate whether 11 candidate single nucleotide polymorphisms (SNPs) in vitamin D and calcium pathway genes (CYP2R1, CYP24A1, and CYP27B1) are associated with the risk of NAFLD.MethodsIn this case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Absence of A allele is associated with insu ciency of Vitamin-D [27,28]. However, until date no association has been reported between CYP2R1 rs10741657 polymorphism and acute to chronic transition of HBV infection neither its association with NAFLD risk [29]. In this study, no any signi cant association was found between CYP2R1 polymorphism and clinical outcomes of HBV infection both in terms of pathophysiological parameter and in terms of disease progression.…”
Section: Detection Of Cyp2r1 Polymorphism At Rs10741657mentioning
confidence: 54%
“…Absence of A allele is associated with insu ciency of Vitamin-D [27,28]. However, until date no association has been reported between CYP2R1 rs10741657 polymorphism and acute to chronic transition of HBV infection neither its association with NAFLD risk [29]. In this study, no any signi cant association was found between CYP2R1 polymorphism and clinical outcomes of HBV infection both in terms of pathophysiological parameter and in terms of disease progression.…”
Section: Detection Of Cyp2r1 Polymorphism At Rs10741657mentioning
confidence: 54%
“…Genome-wide studies have emphasized the role of vitamin D pathway genes in many processes that are strongly linked to NAFLD, such as immunological alteration, cellular differentiation, and inflammatory processes [133,134]. Various genetic studies have revealed frequent single nucleotide polymorphisms (SNPs) in vitamin D pathway genes and highlighted their association with low serum vitamin D levels both in healthy subjects and those with hepatitis, such as the genes for CYP2R1 and CYP27B1 [133], while mutations in the CYP24A1 gene, responsible to vitamin D degradation [135], causes calcitriol elevation [136].…”
Section: The Association Between Nafld and Vddmentioning
confidence: 99%
“…Various genetic studies have revealed frequent single nucleotide polymorphisms (SNPs) in vitamin D pathway genes and highlighted their association with low serum vitamin D levels both in healthy subjects and those with hepatitis, such as the genes for CYP2R1 and CYP27B1 [133], while mutations in the CYP24A1 gene, responsible to vitamin D degradation [135], causes calcitriol elevation [136]. A case-control study that investigated the effect of vitamin D gene SNPs has shown that alleles CYP24A1 rs2296241-A, rs2248359-T, and CYP27B1 rs4646536-T were all considered a risk factor for NAFLD when combined with other clinical factors [134]. Additionally, these alleles were found to co-exist in some NAFLD patients [134].…”
Section: The Association Between Nafld and Vddmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the increased expression of CYP24A1 , a regulator of vitamin D, and the activity of the respective 24-hydroxylase enzyme are associated with the degradation of 25(OH)D 3 into 24.25(OH) 2 D 3 [ 13 ]. CYP24A1 induces low serum levels of 25(OH)D 3 , which has been shown with liver disease severity in studies with non-alcoholic fatty liver disease (NAFLD) [ 14 ] and patients with hepatitis C (HCV) [ 15 ]. Furthermore, some studies suggest that CYP24A1 single nucleotide polymorphisms (SNPs) contributes to a chronic HCV infection, progressing to more defined conditions [ 16 ], such as the risk for liver cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%